2009
DOI: 10.1016/j.molcel.2009.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Telomere Maintenance Component 1 Interacts with STN1 and Maintains Chromosome Ends in Higher Eukaryotes

Abstract: Summary Orthologs of the yeast telomere protein Stn1 are present in plants, but other components of the Cdc13/Stn1/Ten1 (CST) complex have only been found in fungi. Here we report the identification of Conserved Telomere maintenance Component 1 (CTC1) in plants and vertebrates. CTC1 encodes an ∼140 kDa telomere-associated protein predicted to contain multiple OB-fold domains. Arabidopsis mutants null for CTC1 display a severe telomere deprotection phenotype accompanied by a rapid onset of developmental defects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

30
361
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(393 citation statements)
references
References 68 publications
(94 reference statements)
30
361
1
1
Order By: Relevance
“…Recently, it has been shown that CTC1 interacts with STN1 and TEN1 to form the mammalian homolog of the yeast hetero trimeric Cdc13 Stn1 Ten1 (CST) telomeric capping complex 13,14 . Consequently, we also undertook Sanger sequencing of OBFC1 (STN1) and TEN1 in our collection of individuals with Labrune syndrome and in the proband with Coats plus in whom we identified no CTC1 mutations.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, it has been shown that CTC1 interacts with STN1 and TEN1 to form the mammalian homolog of the yeast hetero trimeric Cdc13 Stn1 Ten1 (CST) telomeric capping complex 13,14 . Consequently, we also undertook Sanger sequencing of OBFC1 (STN1) and TEN1 in our collection of individuals with Labrune syndrome and in the proband with Coats plus in whom we identified no CTC1 mutations.…”
mentioning
confidence: 99%
“…In view of the finding of shortened telomeres in an Arabidopsis CTC1 mutant 13 and the phenotypic overlap between Coats plus and the telomeric maintenance disorders comprising dyskeratosis con genita, we measured telomere lengths 15 in F332, F367 and F382 at the ages of 20, 20 and 3 years, respectively. Samples were also available from the mother and heterozygous brother of F367 and from both parents of F332 and F382.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These proteins include the evolutionarily conserved CTC1: STN1: TEN1 (CST) complex. CTC1 and STN1 were originally discovered as proteins that stimulate DNA Pol‐α: primase activity, suggesting an essential role for CST in DNA replication (Casteel et al., 2009; Miyake et al., 2009; Surovtseva et al., 2009). Targeted deletion of CTC1 in the mouse, as well as depletion of individual CST components in human cells, all results in telomere replication defects and global telomere attrition, suggesting that the CST complex is required for multiple steps of telomere replication (Feng, Hsu, Kasbek, Chaiken & Price, 2017; Gu et al., 2012; Wu, Takai & de Lange, 2012).…”
Section: Introductionmentioning
confidence: 99%